An Error Analysis in English Department Students’ Narrative Essay - Dian Eka Sari; Puspita Dewi (Humanitatis : Journal of Language and Literature, 2022)
This study reveals a common error in English department students writing in Indonesia, particularly in one of the private universities in Padang by extracting 25 narrative essays written by the students. The respondents are English department students of STBA Prayoga who are in the fourth semester. This research is conducted to identify the most common grammatical errors within 25 essays that were submitted as writing assignments. They were 16 women and 9 men students in the fourth semester in essay writing subject. The data were collected and identified the errors. The errors are classified into several categories and presented in frequency and percentage. The research results show that one of the most errors in students’ writing is errors in word usage and followed by errors in tense, 38%, and 28% respectively. Meanwhile, errors in using article, preposition, and conjunction are the same percentage, 8%. This research result has good potential for the students and lecturers in the future to identify and use another method in learning and teaching English.